Short-Term Fluoride Release from Ion-Releasing Dental Materials - Llubitza Slaviza Banic Vidal; Nikolina Nika Veček; Ivan Šalinović; Ivana Miletić; Eva Klarić; Silvana Jukić Krmek (University of Zagreb. School of Dental Medicine, 2023)
Objective: To compare short-term release of fluoride ions from ion-releasing dental restorative materials. Material and methods: Seven experimental groups were prepared using the following six different materials: alkasite (Cention Forte), resin-modified glass ionomer cement (Fuji II LC), bioactive composite (ACTIVA BioACTIVE-RESTORATIVE), fluoride-containing nano-hybrid composite (Luminos UN), coat-free glass hybrid (EQUIA Forte HT), coat-applied glass hybrid (EQUIA Forte HT), and glass ionomer cement (Fuji IX). A total of 40 samples for each group (n=40) were prepared in Teflon molds (8 mm x 2 mm) and placed in polyethylene vials with 5 ml of deionized water. Fluoride release was measured after 6, 24, 48 hours, and after 5 weeks using an ion-selective electrode. The results were expressed in mg/l and the data were statistically analyzed using ANOVA. Results: Significant differences in fluoride release were observed within the first 6 hours (ANOVA p<0.001). EQUIA Forte HT had the highest release, while the other materials showed no significant differences. After 24 hours, EQUIA Forte HT (p<0.001) and Luminos UN (p<0.05) exhibited significantly higher releases, compared to other tested materials. EQUIA Forte HT maintained the highest release at 48 hours (p<0.001), followed by Cention Forte (p<0.05) and Luminos UN (p<0.05). All material pairs showed significant differences in fluoride release at 5 weeks (p<0.001). Conclusion: Coat-free EQUIA Forte HT had the overall highest fluoride release, while Cention Forte demonstrated the greatest increase over time. ACTIVA BioACTIVE-RESTORATIVE exhibited the lowest fluoride release in this study.